Pengaruh Penerapan Posisi Semi Fowler Terhadap Frekuensi Napas Pada Pasien Tb Paru Di RS TK Ii Robert Wolter Mongonsidi - Supriyanti Umaternate; Nelfa Fitria Takahepis; Silvia Dewi M. Riu (STIKES Columbia Asia Medan, 2023)
Indonesia is ranked 3rd with the highest TB sufferers in the world after India and China, . According to data from the Ministry of Health (Kemenkes 2021), there are 397,377 cases of tuberculosis (TB) throughout Indonesia. Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium Tuberculosis). Most TB germs attack the lungs but can also attack other organs. The purpose of this study was to determine the effect of semi-fowler positioning on breathing frequency in pulmonary TB patients in hospitals. R.W.Mongosidi This study used a cross-sectional analytical descriptive method. The sample in Ambel was based on the number of respondents as many as 14 people using one group pre-post test design. Data analysis was tested using Wilcoxon. Based on the results of Wilcoxon test analysis, it can be known that the significant value of p value = 0.001 where α = 0.05 can be concluded that there is an effect of semi-fowler positioning on respiratory frequency in pulmonary TB patients. The conclusion in this study is that there is an effect of giving semi-fowler positions on breathing frequency in pulmonary TB patients in hospitals. Robert Wolter Mongosidi. Advice for nurses to use the semi-fowler position on the effectiveness of breathing patterns can be continued or applied to pulmonary TB patients